Installation Effects of Supersonic Inlets on Next-Generation SST Turbofan Engines - Stylianos Adamidis; Dario Del Gatto; Christos Mourouzidis; Stephen Brown; Vassilios Pachidis (Engineering Proceedings, 2025)
This study explores inlet-related installation effects on next-generation SST aircraft, focusing on supersonic business jets. Using a comprehensive framework with consistent thrust/drag bookkeeping and realistic modeling of inlet losses, including operational limits for “buzz” and distortions, the inlet drag accounts for 8.8% to 14.2% of the installed net thrust during the supersonic segment of the mission. Variable airflow control technology is assessed, with a scheduling methodology developed to optimize the inlet operation by minimizing the installed SFC. The results show that this technology improves the installed SFC by 0.80% during supersonic cruise, enhancing the overall propulsion system performance.